A 7mm line survey of the shocked and disrupted molecular gas towards the W28 field TeV gamma-ray sources - Nicholas, B.; Rowell, G.; Burton, M.; Walsh, Andrew; Fukui, Y.; Kawamura, A.; Maxted, N. (Oxford University Press, 2012)
We present 7mm Mopra observations of the dense molecular gas towards the W28 supernovaremnant (SNR) field, following a previous 12mmline survey of this region. These observationstake advantage of the 7mm beam size to probe the dense and disrupted gas in the regionat ~1 arcmin scales. Our observations are focused towards the north-eastern (NE) HESSJ1801-233 and southern HESS J1800-240 B TeV gamma-ray sources, with slightly lessobservations towards HESS J1800-240A and C. Using the CS (1–0) transition we revealmultiple regions of dense gas, nH2~ 105 cm-3. We report the discovery of dense gas towardsHESS J1800-240 C, at the site of a 1720MHz OH maser. The NE molecular cloud is knownto be disrupted; many 1720MHz OH masers and broad CO line emission are detected at therim ofW28. Here, we reveal this shock interaction region contains generally extended clumpyCS, as well as clumpy SiO and CH3OH emission with broad line profiles. The full width at halfmaximum (FWHM) of the molecular lines extend up to 18 km s-1 on the W28 side of the NEcloud. The detection of SiO towards maser clumps OH C, D, E and F provides further evidenceof the shocked conditions in the NE cloud. Several other lines associated with star formationare also detected towards the southern source, notably the energetic HII complex G5.89-0.39.The spatial match of dense gas with the TeV emission further supports the cosmic ray (CR)origin for the gamma-rays. We estimate the mass of several extended dense clouds within thefield and predict the TeV flux from the dense cloud components. The predicted fluxes are of theorder of 10-14 to 10-13 photons cm-2 s-1, which should be detectable and possibly resolvedby a future TeV instrument, such as the Cherenkov Telescope Array.